Food and Beverage Cues Featured in YouTube Videos of Social Media Influencers Popular With Children: An Exploratory Study - Coates, Anna E.; Hardman, Charlotte A.; Halford, Jason C. G.; Christiansen, Paul; Boyland, Emma J. (Frontiers in Psychology, 2019)
Food and beverage cues (visual displays of food or beverage products/brands) featured in traditional broadcast and digital marketing are predominantly for products high in fat, sugar and/or salt (HFSS). YouTube is hugely popular with children, and cues featured in content uploaded by YouTube video bloggers (influencers) has been shown to affect children’s eating behavior. However, little is known about the prevalence of such cues, the contexts in which they appear, and the frequency with which they are featured as part of explicit marketing campaigns. The objective of this study was to explore the extent and nature of food and beverage cues featured in YouTube videos of influencers popular with children. All videos uploaded by two influencers (one female, one male) over a year (2017) were analyzed. Based on previous content analyses of broadcast marketing, cues were categorized by product type and classified as ‘healthy’ or ‘less healthy’ according to the UK Nutrient Profiling Model. Cues were also coded for branding status, and other factors related to their display (e.g. description). In total, the sample comprised 380 YouTube videos (119.5 hours) and, of these, only 27 videos (7.4%) did not feature any food or beverage cues. Cakes (9.4%) and fast foods (8.9%) were the most frequently featured product types, less frequent were healthier products such as fruits (6.5%) and vegetables (5.8%). Overall, cues were more frequently classified as less healthy (49.4%) than healthy (34.5%) and were presented in different contexts according to nutritional profile. Less healthy foods (compared with healthy foods) were more often; branded, presented in the context of eating out, described positively, not consumed, and featured as part of an explicit marketing campaign. These data provide the first empirical assessment of the extent and nature of food and beverage cue presentation in YouTube videos by influencers popular with children. Given the emerging evidence of the effects of influencer marketing of food and beverages on children’s eating behavior, this exploratory study offers a novel methodological platform for digital food marketing assessment and delivers important contextual information that could inform policy deliberations in this area.